2013
DOI: 10.3892/or.2013.2850
|View full text |Cite
|
Sign up to set email alerts
|

Role of long non-coding RNA HULC in cell proliferation, apoptosis and tumor metastasis of gastric cancer: A clinical and in vitro investigation

Abstract: Long non-coding RNAs (lncRNAs) are emerging as key molecules in human cancer. Highly upregulated in liver cancer (HULC), an lncRNA, has recently been revealed to be involved in hepatocellular carcinoma development and progression. It remains unclear, however, whether HULC plays an oncogenic role in human gastric cancer (GC). In the present study, we demonstrated that HULC was significantly overexpressed in GC cell lines and GC tissues compared with normal controls, and this overexpression was correlated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
225
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(233 citation statements)
references
References 35 publications
7
225
0
1
Order By: Relevance
“…Recent studies have shown that microRNAs in the miR-200 family, miR-101 and miR-506 are markedly downregulated during EMT and also strong regulators of EMT through regulating transcription factors involved in EMT (22)(23)(24). Similarly, several lncRNAs are found to induce EMT, including HULC, MALAT-1, H19, and HOTAIR (25)(26)(27)(28). These genes and RNAs are often recognized as markers for EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that microRNAs in the miR-200 family, miR-101 and miR-506 are markedly downregulated during EMT and also strong regulators of EMT through regulating transcription factors involved in EMT (22)(23)(24). Similarly, several lncRNAs are found to induce EMT, including HULC, MALAT-1, H19, and HOTAIR (25)(26)(27)(28). These genes and RNAs are often recognized as markers for EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Lung Upregulated [190] Suppression of E-cadherin [191] Bladder Upregulated [192] Breast Upregulated [193] Pancreatic Upregulated [194] MEG3 Meningioma Downregulated [195] Regulation of autophagy [196] and DNA repair [197] Lung Downregulated [198] Gastric Downregulated [199] HOTAIR Liver Upregulated [200] Reprogramming of chromatin state [201,202] Breast Upregulated [203] Pancreatic Upregulated [204] GAS5 Liver Downregulated [205] Controls invasion by control of miRNAs [205,206] Gastric Downregulated [207] Breast Downregulated [208] H19 Liver Upregulated [209] Chromatin remodeling [210] and TGF-β regulation [211] Pancreatic Upregulated [137,212] Gastric Upregulated [213] HULC Liver Upregulated [147] Regulates tumor microenvironment interactions [214] Gastric Upregulated [148] Breast Upregulated [92,146] SPRY4-IT1 Melanoma Upregulated [139] Proliferation and invasion via regulation of EZH2 [143] Lung Upregulated [215] SCC Upregulated [142] and LBR to initiate transcriptional silencing [77] . Taken together, it is crucial that these biochemistry-focused studies continue, such that, novel therapies can be developed to modulate a specific biological activity mediated by a particular lncRNA of interest.…”
Section: Malat1mentioning
confidence: 99%
“…Two recent studies suggest that HULC promotes angiogenesis as well as neo-angiogenesis, essential processes in the progression of metastasis as micro-metastatic lesions require an oxygen-rich environment to meet the demand of tumor growth within an hypoxic environment. For instance, Zhao et al [148] found that overexpression of HULC in hepatocellular cancer cells results in an increase in the pro-angiogenic factor SPHK1. Specifically, HULC functions by sequestering miR-107, a bona fide target of which is the TF E2F1.…”
Section: Highly Upregulated In Liver Cancermentioning
confidence: 99%
“…However, recent research suggested some serum non-coding RNA could also be potential gastric specific markers. Long non-coding RNA HULC and H19 were reported to be promising novel biomarkers in plasma of patients with gastric cancer [70][71][72][73][74][75]. MicroRNA is a relatively stable species of RNA in the serum.…”
Section: Rna Markers Of Gastric Cancermentioning
confidence: 99%